2011
DOI: 10.1074/mcp.m110.006353
|View full text |Cite
|
Sign up to set email alerts
|

A High-Confidence Human Plasma Proteome Reference Set with Estimated Concentrations in PeptideAtlas

Abstract: Human blood plasma can be obtained relatively noninvasively and contains proteins from most, if not all, tissues of the body. Therefore, an extensive, quantitative catalog of plasma proteins is an important starting point for the discovery of disease biomarkers. In 2005, we showed that different proteomics measurements using different sample preparation and analysis techniques identify significantly different sets of proteins, and that a comprehensive plasma proteome can be compiled only by combining data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
494
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 394 publications
(516 citation statements)
references
References 61 publications
16
494
1
1
Order By: Relevance
“…Cross-referencing these lists with lists of proteins previously reported as being present in the blood of healthy individuals (19) revealed that 29 neuron-specific genes were present in blood; 13 of these were brain-specific as well (Dataset S3). We believe that concentrations of the brain-specific blood proteins could change during disease or injury (presumably reflecting the activity of disease-perturbed biological networks), or that disease or injury could cause brain-specific proteins not normally found in the blood to be secreted.…”
Section: Transcriptomic Signatures Distinguishing Cortical and Noncormentioning
confidence: 99%
“…Cross-referencing these lists with lists of proteins previously reported as being present in the blood of healthy individuals (19) revealed that 29 neuron-specific genes were present in blood; 13 of these were brain-specific as well (Dataset S3). We believe that concentrations of the brain-specific blood proteins could change during disease or injury (presumably reflecting the activity of disease-perturbed biological networks), or that disease or injury could cause brain-specific proteins not normally found in the blood to be secreted.…”
Section: Transcriptomic Signatures Distinguishing Cortical and Noncormentioning
confidence: 99%
“…Latter approaches might miss protein identifications that are falsely discarded by the a priori grouping scheme or the parsimony constraint. Instead of disambiguating ambiguous peptide identifications, Farrah et al report all proteins consistent with the spectral data (42). To be able to make statements about the occurrence of proteins in the biological sample, the authors of this study introduced the CEDAR scheme for protein identifications.…”
Section: Solutionsmentioning
confidence: 99%
“…In this analogy the first type of balls represents the protein entries for which there is correct support and the other type represents all other entries of the underlying protein database. Mayu has shown to achieve accurate, independently validated protein identification false discovery rates for a range of diverse datasets differing in size, underlying proteome and experimental setting (53) and been added as additional feature to PeptideAtlas (42).…”
Section: Validationmentioning
confidence: 99%
“…For 2-aminobenzoic acid (AA) labeling, the dried, purified glycan samples were dissolved in 50 μl water and mixed with 25 μl of a freshly prepared label solution (48 mg/ml AA in DMSO containing 15% glacial acetic acid) (29). Twenty-five μl aliquots of freshly prepared reducing agent solution (1 M 2-picoline borane in DMSO) were added, followed by 10 min of Carlsson et al,page 8 shaking and incubation at 65°C for 2h.…”
Section: Glycan Labeling and Purificationmentioning
confidence: 99%